Posttransplant sCD30 as a predictor of kidney graft outcome - Süsal, Caner; Döhler, Bernd; Sadeghi, Mahmoud; Salmela, Kaija T.; Weimer, Rolf; Zeier, Martin; Opelz, Gerhard (Transplantation, 2011)
Background. - Reliable markers for assessing the biological effect of immunosuppressive drugs and identification of transplant recipients at risk of developing rejection are not available. - Methods. - In a prospective multicenter study, we investigated whether posttransplant measurement of the T-cell activation marker soluble CD30 (sCD30) can be used for estimating the risk of graft loss in kidney transplant recipients. Pre- and posttransplant sera of 2322 adult deceased-donor kidney recipients were tested for serum sCD30 content using a commercial enzyme-linked immunosorbent assay. - Results. - sCD30 decreased posttransplant and reached a nadir on day 30. Patients with a high sCD30 of more than or equal to 40 U/mL on day 30 showed a subsequent graft survival rate after 3 years of 78.3±4.1%, significantly lower than the 90.3±1.0% rate in recipients with a low sCD30 on day 30 of less than 40 U/mL (log-rank P<0.001; Cox hazard ratio 2.02, P<0.001). Although an association was found between pre- and posttransplant sCD30 levels, patients with high sCD30 on posttransplant day 30 demonstrated significantly lower 3-year graft survival irrespective of the pretransplant level. - Conclusions. - Our data suggest that posttransplant measurement of sCD30 on day 30 is a predictor of subsequent graft loss in kidney transplant recipients and that sCD30 may potentially serve as an indicator for adjustment of immunosuppressive medication.
Gesehen am 26.10.2022